Three-Dimensional EGM Study on Shielding Failure Rate of Transmission Lines Considering Canyon Depth - Jieting BI (Zhongguo dianli)
A considerable number of high voltage transmission lines are built across deep valleys. In the past, no specific study was carried out on the valley topography in building models for calculating shielding failure rate of transmission lines, and the shielding effect of the unique topography of valleys was ignored. In this paper, a new three-dimensional electrical geometrical model (EGM) based on valley depth is established to directly study the transmission line shielding failure rate through calculating the exposed and protected cambered surface areas. The effectiveness of the proposed three-dimensional EGM method is verified through an example, and the valley topography is proved to be one of the main causes for frequent lightning trip-out of transmission lines. Avoiding complicated calculus operation, the proposed method is mainly applicable in mountain valley area. With consideration of the canyon depth and the slope angle of the ground, the calculated shielding failure rate is closer to the actual situation, which is significant for application.